Karen youth transitions at the Thai-Myanmar border - Jolliffe, P (Routledge, 2017)
This article examines youth transitions within a context of forced migration including rural areas in Eastern Myanmar and temporary shelters for displaced persons at the Thai-Myanmar border, as well as a Jesuit education project in Chiang Mai province. The study is informed by a life course approach that emphasizes the interlinkage between individual biographies and socio-political developments. Drawing on qualitative research methods such as participant observation, participatory research methods, essay writing and informal interviews, research data highlight the pivotal role of formal education even in a context of war and displacement. Making the vertical transition from one school stage to the next gives meaning and structure to the lives of the displaced youth who participated in this study and shapes their horizontal transitions between different geographical and social spaces along the Thai-Myanmar border. In this respect the study suggests that within the continuum of displacement at the Thai-Myanmar border ethnicity and citizenship status, coupled with social relations and individual skills for institutional networking, predominantly shape young Karen womeńs and meńs pursuit for education, as well as their decisions to interrupt their studies for transition to work.